Paradoxos do motor : uma esquizoanálise da atividade dos motoristas de ônibus do transporte coletivo urbano da Grande Vitória-ES - Zamboni, Jésio (2011)
This dissertation consists of a series of articles, developed from the analysis of the activity of urban mass-transit bus drivers in Grande Vitória, Espírito Santo, Brazil. The texts are composed based on paradoxes, which are problematic axes of the work of the bus driver and of the intervention-research conducted by us with the workers. The “Epigraph” brings the paradox of let down, so that there are not expectations of a great event from this research and one could walk to the beat of a song while reading. The “Acknowledgments” operates as an outside-the-text, indicating a number of institutional crossings that constitute the figure of schizoanalyst clinician of activity, through the paradox of jest. In “Passages”, the researcher assumes position of passenger, to work on the paradox of the bus driver as first passenger, highlighting some hints for the study of relations between activity and subjectivity through labor processes. “Jump the turnstile” refers, through the paradox of the drivers who struggle working, to work activity as a possible focus for collective struggles for the transformation of urban public transportation. “Ethics and the desiring-motor” approaches the ethical dimension, from the paradox of the crossed-out names, emphasizing, through the relationship between clinician and bus drivers, the warfare intrinsic to the work environment. “Analysis of the activity by chatting” discusses the construction of the device of scattered conversations, in which the paradox of the dancing driver is forged, as a research method and a means of self-analysis for the drivers. “The activity of the bus driver” configures the central problem of the research, bringing analysis of the daily work into the scene through the paradox of the questions without answers. The “Corporateness” refers to the collective dimension of the work of the urban mass-transit bus driver, dismantling the established corporate sense to think about building an ethical body of the worker. “Micropolitics of activity” develops the paradox of the analytical tool, through the theoretical consequences of the research with the bus drivers about their work, in order to promote conceptual and technical modulations, around the concept of activity, central to this intervention. “Schizoanalysis of ergonomics” continues the conceptual and technical discussion, developing around the paradox the concept of man-machine system, by Maurice de Montmollin, appropriated by Gilles Deleuze & Félix Guattari. Then, about the paradox of the archangel Michael, the intersection between “Clinic of activity and philosophy of difference” is developed on the basis of analysis of productive activity, considered as desiring and social. “Gilles Deleuze, clinician of philosophical activity” and “Clinic of the psychoanalytic activity by Felix Guattari” take into account the contributions of a conceptual worker and of an analyst of desiring activities in the social field, respectively, to support the paradoxes of the philosopher workman and of the militant analyst as possible figures for the clinician schizoanalyst of activity. “An angel who kills the pain”, the paradox of the epilogue to this collection of articles gathered as dissertation, is an homage to an interlocutor bus driver, who is writing his biography marked by his existence in the field of work.